Governance of a fragile Eurozone - De Grauwe, Paul (Brussels, 2011)
"When entering a monetary union, member countries change the nature of their sovereign debt in a fundamental way, i.e. they cease to have control over the currency in which their debt is issued. As a result, financial markets can force these countries’ sovereigns into default. In this sense, the status of member countries of a monetary union is downgraded to that of an emerging economy. This makes the monetary union fragile and vulnerable to changing market sentiments. It also makes it possible that self-fulfilling multiple equilibria arise. This paper analyses the implications of this fragility for the governance of the eurozone. It concludes that the new governance structure (ESM) does not sufficiently recognize this fragility. Some of the features of the new financial assistance in fact are likely to increase this fragility. In addition, it is also likely to prevent member countries from using the automatic stabilizers during a recession. This is surely a step backward in the long history of social progress in Europe. The author suggests a different approach to deal with these problems."